Kinematic analysis of the technique for 500-m speed skaters in curving - Song, J.-H.; Park, J.-C.; Kim, J.-S. (Korean Journal of Sport Biomechanics, 2018)
Objective: The purpose of this study is to analyze the kinematic characteristics of the national speed skaters in the curve phase of 500-m race.